Use of Polyols in Dentistry: Effects on Tooth Mineral Dynamics and Oral Biofilms - Zen, Igor [UNESP]; Martins, Tamires Passadori [UNESP]; Sampaio, Caio [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Monteiro, Douglas Roberto [UNESP]; Pessan, Juliano Pelim [UNESP] (Wiley, 2023)
Natural products have been used in several fields in dentistry due to their therapeutic effects. Among the options available, xylitol and erythritol are sugar alcohols (polyols) that have anticaries properties, as they reduce biofilm acidogenicity and plaque accumulation, and interfere with the composition of the extracellular matrix. In addition to their effects on biofilms, these polyols act on the de- and re-mineralization processes due to the binding capacity between calcium and xylitol. In the literature, different study protocols have demonstrated the effects of these polyols when administered as candies, chewing gums, lozenges, mouthwashes and dentifrices. This chapter will present the main data on xylitol and erythritol from studies performed in vitro and in situ, in addition to randomized clinical trials addressing their effects on caries-related variables such as dental biofilm and enamel de- and re-mineralization processes. Insights on their mechanisms of action and future steps for research will also be addressed.
Keywords: biofilms; dental caries; Sugar alcohols; tooth remineralization